Post-ST-Segment Elevation Myocardial Infarction Follow-Up Care During the COVID-19 Pandemic and the Possible Benefit of Telemedicine: An Observational Study - Zhang, Audrey A. Y.; Chew, Nicholas W. S.; Ng, Cheng Han; Phua, Kailun; Aye, Yin Nwe; Mai, Aaron; Kong, Gwyneth; Saw, Kalyar; Wong, Raymond C. C.; Kong, William K. F.; Poh, Kian-Keong; Chan, Koo-Hui; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Infectious control measures during the COVID-19 pandemic have led to the propensity toward telemedicine. This study examined the impact of telemedicine during the pandemic on the long-term outcomes of ST-segment elevation myocardial infarction (STEMI) patients. Methods: This study included 288 patients admitted 1 year before the pandemic (October 2018–December 2018) and during the pandemic (January 2020–March 2020) eras, and survived their index STEMI admission. The follow-up period was 1 year. One-year primary safety endpoint was all-cause mortality. Secondary safety endpoints were cardiac readmissions for unplanned revascularisation, non-fatal myocardial infarction, heart failure, arrythmia, unstable angina. Major adverse cardiovascular events (MACE) was defined as the composite outcome of each individual safety endpoint. Results: Despite unfavorable in-hospital outcomes among patients admitted during the pandemic compared to pre-pandemic era, both groups had similar 1-year all-cause mortality (11.2 vs. 8.5%, respectively, p = 0.454) but higher cardiac-related (14.1 vs. 5.1%, p < 0.001) and heart failure readmissions in the pandemic vs. pre-pandemic groups (7.1 vs. 1.7%, p = 0.037). Follow-up was more frequently conducted via teleconsultations (1.2 vs. 0.2 per patient/year, p = 0.001), with reduction in physical consultations (2.1 vs. 2.6 per patient/year, p = 0.043), during the pandemic vs. pre-pandemic era. Majority achieved guideline-directed medical therapy (GDMT) during pandemic vs. pre-pandemic era (75.9 vs. 61.6%, p = 0.010). Multivariable Cox regression demonstrated achieving medication target doses (HR 0.387, 95% CI 0.164–0.915, p = 0.031) and GDMT (HR 0.271, 95% CI 0.134–0.548, p < 0.001) were independent predictors of lower 1-year MACE after adjustment. Conclusion: The pandemic has led to the wider application of teleconsultation, with increased adherence to GDMT, enhanced medication target dosing. Achieving GDMT was associated with favorable long-term prognosis.